PENGAMBILAN KEPUTUSAN RUMAH TANGGA DALAM MENGONSUMSI KECAP MANIS DI KOTA BANDAR LAMPUNG - Vemy Ratna Dewi; Yaktiworo Indriani; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research aims to analyze the preferred attributes, purchasing patterns, and factors that influenced soybean sauce demand of household consumer in Bandar Lampung City. This research employed survey method using qualitative and quantitative analyses.  The location was determined by stage groups. The total samples were 75 housewives who were drawn randomly and served as respondents. The preferred attributes of soy sauce by households was analyzed by conjoint analysis; purchase patterns of soybean sauce was analyzed by identifying and tabulating data; and the influencing factors of soybean sauce demand were analyzed by Cobb Douglas function. The research results showed that the attributes most respondents considered when buying soybean sauce were color, taste, size, and package; namely brownish black color, not too sweet taste, less than 200 ml volume and plastic sachet/refill package.  Most households chose ‘Bango’, ‘ABC’, and ‘Sedaap’ soybean sauce brand because of  their good taste, cheap price, consumer’s habit, and the only brand available at their nearby smallstores, regardless of the nutrients contained in the soybean sauce.  The housewives usually purchase it in nearby smallstores, market, and supermarket.  They bought it twice, more than twice, or once per month.  Respondents consumed it for seasoning and for eating it with rice, with the purchase of as much as 400-700 ml, 100-400 ml, or 700-1000 ml/month.  The factors that influenced  soybean sauce demand together were the price, granulated sugar price, brown sugar price, respondent’s education level, the number of household members, brand, and neighborhood. Keywords:  household decision making, purchase patterns, soybean sauce